2021
DOI: 10.3390/ijerph18137071
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Association of Social Disadvantage and Cerebrovascular Disease Confirmed by Neuroimaging and Neuropathology

Abstract: Social disadvantage—a state of low-income, limited education, poor living conditions, or limited social support—mediates chronic health conditions, including cerebrovascular disease. Social disadvantage is a key component in several health impact frameworks, providing explanations for how individual-level factors interact with interpersonal and environmental factors to create health disparities. Understanding the association between social disadvantage and vascular neuropathology, brain lesions identified by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Our findings are consistent with other reviews examining the impact of area-based disadvantage on various outcomes. A recent scoping review of the effect of social disadvantage on neuropathologically confirmed cerebrovascular disease found a lack of longitudinal study designs and inconsistent methodologies overall [22]. A European review of the association between area-level disadvantage and suicidal behaviors found only one longitudinal study that met their inclusion criteria [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other reviews examining the impact of area-based disadvantage on various outcomes. A recent scoping review of the effect of social disadvantage on neuropathologically confirmed cerebrovascular disease found a lack of longitudinal study designs and inconsistent methodologies overall [22]. A European review of the association between area-level disadvantage and suicidal behaviors found only one longitudinal study that met their inclusion criteria [23].…”
Section: Discussionmentioning
confidence: 99%